Investigating Genetic and Phenotypic Variability of Queen Bees: Morphological and Reproductive Traits - Elena Facchini (MDPI AG, 2021)
The quality of the honeybee queen has an important effect on a colony’s development, productivity, and survival. Queen failure or loss is considered a leading cause for colonies’ mortality worldwide. The queen’s quality, resulting from her genetic background, developmental conditions, mating success, and environment, can be assessed by some morphological measures. The study aims to investigate variability for traits that could assess the quality of the queen. Related animals were enrolled in this study. Variance components were estimated fitting a mixed animal model to collected data. Heritabilities of body and tagmata weights ranged from 0.46 to 0.54, whereas lower estimates were found for the tagmata width and wing length. Heritabilities estimated for the spermatheca diameter and volume, number of ovarioles, and number of sperms were 0.17, 0.88, 0.70, and 0.57, respectively. Many phenotypic correlations related to size were high and positive, while weak correlations were found between morphology and reproductive traits. Introducing a queen’s traits in a selection program could improve colonies’ survivability. Further research should focus on better defining the correlations between the individual qualities of a queen and her colony’s performance.